2013
DOI: 10.1007/s10164-013-0365-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in sexual behavior of two distant populations of the funnel-web wolf spider Aglaoctenus lagotis

Abstract: Generally, sexual repertoire within a species is conserved, but frequencies of occurrence of sexual behavioral acts often vary, and wide geographic distributions may favor these variations. Aglaoctenus lagotis is distributed along South America and belongs to Sosippinae, a subfamily of wolf spiders that builds funnel webs. Previous reports, based on different populations, suggested variations in sexual behavior and life cycle. Our objective was to describe and compare the sexual behavior of two populations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 69 publications
3
45
1
1
Order By: Relevance
“…Additionally, Santos & Brescovit () characterized A. lagotis as a highly variable species, although no interpopulation studies were reported prior to González et al . ().…”
Section: Introductioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Additionally, Santos & Brescovit () characterized A. lagotis as a highly variable species, although no interpopulation studies were reported prior to González et al . ().…”
Section: Introductioncontrasting
confidence: 65%
“…González et al . () described different sexual repertoires in two distant populations of A. lagotis (south Uruguay and central Argentina), both of which were dissimilar to the description published by Stefani et al . () for populations from Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, we could not explain the unexpected higher implant cover percentage recorded for weaving females compared to those prevented from weaving. Perhaps the dimensions of the tubes selected for preventing weaving are too small for females, which are larger than subadults and males (Gonzá lez et al 2013), making confinement stressful (and probably indirectly affecting immune cost). Another consideration might be that females who wove coincidently had better body conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The species is widely distributed, from Uruguay to Colombia (Piacentini 2011), being present in different environments (Sordi 1996;Santos & Brescovit 2001). The existence of two forms has been reported within the species, differing from each other at least in sexual behavior (Gonzá lez et al 2013) and phenology (Gonzá lez et al 2014), suggesting a divergence process (Gonzá lez et al 2015). One of the forms (the ''similar to southern Uruguay, SU'') constructs its webs exclusively on the herbaceous stratum, and the other (the ''similar to central Argentina, CA'') can construct them also on the arbustive and arboreal strata (Gonzá lez et al 2014).…”
mentioning
confidence: 99%